Pengaruh Sekolah Berbasis Lingkungan Terhadap Akhlak Peduli Lingkungan Peserta Didik MIN Pucangsimo Bandar Kedungmulyo Jombang - Adibah Adibah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2019)
This study aims to find the Effect of Environmental-Based Schools on the Morality of the Environment of Students in MIN Pucangsimo Bandar Kedungmulyo Jombang. This type of research is quantitative descriptive, with data collection techniques of observation, interviews, questionnaires and documentation. The data analysis technique uses the product moment correlation analysis technique. Based on the test results with product moment correlation obtained r = 0.3828703 with db = 52 (n-2). This finding found that there was a very significant correlation between environment-based schools and environmental awareness. Thus Ho (null hypothesis) proposed is rejected and HÉ‘ (alternative hypothesis) is accepted. Which means that there is a Very Significant Positive Effect on the Environment-Based School on the Morality of the Environment of Students in MIN Pucangsimo Bandar Kedungmulyo Jombang.